2017
DOI: 10.1542/hpeds.2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Costs and Charges of Discharge Delays in Children Hospitalized for Abuse and Neglect

Abstract: Continued hospitalization beyond medical clearance occurs often and represents a significant cost. Further study is needed to evaluate whether interventions can be targeted at children with characteristics correlated with prolonged discharge delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Other studies have documented longer lengths of stay for children hospitalized with abusive injuries (Russo et al, 2008). A study conducted in a large children’s hospital in Texas found that 1 in 5 abused children experienced a delay of discharge after medical clearance by greater than 1 day, many related to child welfare placement (Lee et al, 2017). In addition to longer lengths of stay, the decision to admit a child for hospitalization may also be influenced by the complex social disposition of patients with suspected abusive injuries in order to ensure a safe and appropriate placement where the child is not at risk for further abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have documented longer lengths of stay for children hospitalized with abusive injuries (Russo et al, 2008). A study conducted in a large children’s hospital in Texas found that 1 in 5 abused children experienced a delay of discharge after medical clearance by greater than 1 day, many related to child welfare placement (Lee et al, 2017). In addition to longer lengths of stay, the decision to admit a child for hospitalization may also be influenced by the complex social disposition of patients with suspected abusive injuries in order to ensure a safe and appropriate placement where the child is not at risk for further abuse.…”
Section: Discussionmentioning
confidence: 99%
“…En-Pei Lee et al retrospectively reviewed cases of child maltreatment admitted to Chang Gung Memorial Hospital at Linkou from 2001 to 2015 and observed that the abusive trauma group had longer stays in the ICU than the neglectful trauma group (18.2±23.9 days vs 7.2±6.9 days respectively, p<0.01), and often a worse prognosis [13]. Children who were diagnosed as abused or neglected were more likely to die during hospitalization, have longer hospital stays, and have greater medical expenses [14][15][16][17][18]. These were compatible with our outcome analysis which neglected patients tended to have significantly better outcome and shorter ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…These were compatible with our outcome analysis which neglected patients tended to have significantly better outcome and shorter ICU stay. Furthermore, some discharges were delayed despite medical clearance due to a lack of safe deposition [17]. Referral to multidisciplinary child protective service organizations significantly reduces the avoidable days of hospitalization and health care waste [19].…”
Section: Discussionmentioning
confidence: 99%
“…The process of child protective services obtaining legal custody and/or identifying a safety plan including a foster caregiver may extend beyond the time period required for resolution of medical issues. 17 Thus, once the foster caregiver is identified, discharge may occur relatively quickly, often without time for foster caregivers to actively participate in patient care in the hospital with the child. In some cases, the child protective services representative may accompany the child from the hospital to the foster caregiver, such that information Length of stay was included in final regressions for communication with PCP, follow-up call completed, misunderstandings at follow-up call, and readmissions.…”
Section: Discussionmentioning
confidence: 99%